Effectiveness of Cupping Aromatherapy Nanoemulsion on Mean Arterial Pressure and Heart Rate in Hypertension Patients - Aris Setyawan; Kintoko Kintoko; Wahyudi Widada (Indonesian Journal of Global Health Research, 2025)
Hypertension is a cardiovascular disease that contributes to increased morbidity and mortality rates. Pharmacological therapy often causes side effects and decreases patient compliance, so a safe and effective complementary treatment approach is needed. Therapy is known to have physiological effects on the cardiovascular system, while aromatherapy has relaxing and vasodilatory effects. The development of aromatherapy in the form of nanoemulsion is expected to increase the stability and effectiveness of therapy, especially when combined with cupping therapy. This study aims to determine the effectiveness of nano aromatherapy cupping on mean arterial pressure (MAP) and heart rate in hypertensive patients. The study used a quasi-experimental design with a pretest-posttest control group design. The sampling method used random sampling, as many as 30 hypertensive patients were divided into two groups: the intervention group that received cupping therapy and aromatherapy nanoemulsion, and the control group that only received cupping therapy. The dependent variables included mean arterial pressure (MAP) and heart rate measured before and after the intervention. Data analysis used the T test. The results showed a significant decrease in MAP and heart rate in both groups after the intervention (p < 0.05). However, the results of the inter-group test showed that the difference in the decrease in MAP and heart rate between the intervention and control groups was not statistically significant (p > 0.05). The conclusion of this study shows that cupping therapy with aromatherapy nanoemulsion is effective in reducing MAP and heart rate in hypertensive patients.